2010
DOI: 10.1007/s00464-010-1424-0
|View full text |Cite
|
Sign up to set email alerts
|

Transoral parathyroid surgery—feasible!

Abstract: We read with interest the letter of Benhidjeb and colleagues [1] in response to our article [2] and are grateful for the opportunity to reply. Benhidjeb and colleagues criticize our claim to the first description of an entirely transoral access for hemithyroidectomy and parathyroidectomy without an accessorial incision of the skin in pigs and human cadavers as wrong. We respectfully disagree.Our project, Transoral Thyroid and Parathyroid Surgery, initially called NOTES-PTX and focused especially on parathyroid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 11 publications
0
2
0
1
Order By: Relevance
“…[19] Later, in human studies, Karakas et al , reported 3/5 (60%) success as TOPP was converted to conventional open technique in two cases. [20] Median operative time reported in that study was 122 min with haematoma of the floor of the mouth in three cases. One patient had transient recurrent laryngeal nerve palsy and another had transient hypoglossal nerve palsy.…”
Section: Discussionmentioning
confidence: 97%
“…[19] Later, in human studies, Karakas et al , reported 3/5 (60%) success as TOPP was converted to conventional open technique in two cases. [20] Median operative time reported in that study was 122 min with haematoma of the floor of the mouth in three cases. One patient had transient recurrent laryngeal nerve palsy and another had transient hypoglossal nerve palsy.…”
Section: Discussionmentioning
confidence: 97%
“…23,24 Bhargava et al have also demonstrated that with proper case selection, the transoral TOEPVA technique is an alternative for parathyroidectomy especially for unigland sporadic primary hyoerparathyroidism. 25 Transient recurrent laryngeal nerve palsy was reported in one case by Karakas et al One of our patients who developed recurrent laryngeal nerve paresis in the postoperative period recovered over a period of time. 26 In literature, gas related complications like hypercarbia, subcutaneous emphysema, mediastinal emphysema and cardiac arrhythmias have been mentioned.…”
Section: Discussionmentioning
confidence: 57%
“…В ис-следованиях были определены значительные технические ограничения, связанные с повышенным риском развития осложнений, особенно при тиреоидэктомии. В то же время отмечено, что выполнение паратиреоидэктомии из трансорального доступа может быть более безопасным и перспективным [15][16][17][18][19][20].…”
unclassified